OBLIKOVAJE PRVIH VZORCEV PRAVIŠKIH BESEDIL V SLOVEŠČII I JIHOVA RABA V PRAKSI (Filološke studije, 2019)
The article represents a historical examination of Slovene legal language in the period 1848 – 1900. The main attention is devoted to planned development of patterns for Slovene legalistic texts. Analysis is based on the research corpus, which consists of Slovene legalistic texts, preserved in the Slovene national archive.